1997
DOI: 10.1177/039139889702000403
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Associated Hypoxia Extends into the Post-Dialysis Period

Abstract: To investigate whether hypoxia extends into the post-hemodialysis period, nine clinically stable-end stage renal disease patients were dialyzed against bicarbonate and one against an acetate batch, all with bioincompatible dialyzers. None had clinical evidence of cardiopulmonary overload on the day of the study. Using an oximeter with internal memory, oxygen saturation was monitored continuously at the beginning, during, and for four hours after hemodialysis. Hypoxia was defined as oxygen saturation less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Those with diabetes demonstrated a significantly higher median relative blood flow at 6 mm tissue depth [25 vs. 14 arbitrary units (AU) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14); P = 0.048] at baseline compared with the non-diabetic group (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those with diabetes demonstrated a significantly higher median relative blood flow at 6 mm tissue depth [25 vs. 14 arbitrary units (AU) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14); P = 0.048] at baseline compared with the non-diabetic group (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the increase in incidence of new foot ulcers may be in part the result of haemodialysis itself [2]. It has been known for many years that haemodialysis is associated with generalized hypoxaemia [4][5][6][7], but the cause is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is thought to occur due to various factors, including pulmonary microatelectasis, the activation of complement, and a change in the oxygen dissociation curve. [62] Nonetheless, the direct effect of hemodialysis should not lead to an underestimation of perturbations associated with diabetes. [63,64] Among patients with various kidney diseases requiring dialysis, diabetes significantly increases the risk for amputation by 2.51-6.4.…”
Section: The Diabetic Foot In Esrdmentioning
confidence: 99%
“…Hypoxia during HD has been previously reported, and it is usually attributed to acetate and sometimes, a bicarbonate bath (29)(30)(31). However, an important component driving hypoxia could be volume overload.…”
Section: Discussionmentioning
confidence: 99%